2017
DOI: 10.21451/1984-3143-ar907
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic and extrinsic factors that influence ovarian environment and efficiency of reproduction in cattle

Abstract: All the somatic cells composing a mammalian organism are genetically identical and contain the same DNA sequence. Nevertheless, they are able to adopt a distinct commitment, differentiate in a tissue specific way and respond to developmental cues, acquiring a terminal phenotype. At the end of the differentiation process, each cell is highly specialized and committed to a distinct determined fate. This is possible thanks to tissue-specific gene expression, timely regulated by epigenetic modifications, that grad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
11
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 44 publications
1
11
0
1
Order By: Relevance
“…In addition to the reduced number of small follicles, the findings showed that HS negatively affected the number of medium follicles (6 -9 mm diameter), which is consistent with other studies [15]. The decreased number of medium follicles is an indication that HS depresses follicular dominance in the first and second follicular wave [26]. Mediums follicles are sensitive indicators of follicular dominance since the dominant follicle inhibits the growth of subordinate follicles [31].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…In addition to the reduced number of small follicles, the findings showed that HS negatively affected the number of medium follicles (6 -9 mm diameter), which is consistent with other studies [15]. The decreased number of medium follicles is an indication that HS depresses follicular dominance in the first and second follicular wave [26]. Mediums follicles are sensitive indicators of follicular dominance since the dominant follicle inhibits the growth of subordinate follicles [31].…”
Section: Discussionsupporting
confidence: 84%
“…The development of follicles has been reported to be damaged [26] or altered [27] by HS during folliculogenesis, with a delayed negative effect on ovarian function. Decreased LH pulse and frequency have been reported because of HS [28].…”
Section: Discussionmentioning
confidence: 99%
“…In vitro fertilization and cattle embryo production are common practices in beef cattle production systems, especially in Zebu breeds [ 13 , 14 , 15 ]. The measurement of AMH concentration and its association with reproductive and fertility traits were widely studied in livestock, including cattle [ 16 , 17 , 18 , 19 , 20 , 21 ]. These studies indicated that circulating AMH levels are a useful indicator of fertility and reproductive performance.…”
Section: Introductionmentioning
confidence: 99%
“…These studies indicated that circulating AMH levels are a useful indicator of fertility and reproductive performance. The role of AMH in different aspects of reproductive physiology is noteworthy, and it is involved with AFP [ 16 , 22 ], superovulation responses [ 23 ], in vitro embryo production [ 10 , 24 , 25 ], fertility traits (i.e., age at puberty and postpartum interval) [ 26 ], and longevity [ 27 ] in beef cattle. The definition and use of efficient biological indicators of fertility is a promising path to increase the success of reproductive technologies (e.g., embryo transfer, superovulatory responses), especially in Nellore cattle raised in tropical conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of reported dataindicates that the effectiveness of the response of the ovaries of embryo donor cows to the exogenous gonadotropin is influenced by many factors [18]. The major are the breed and physiological state of the animals [19,20], especially metabolic [21] and hormonal status [22][23][24][25], genetic predisposition [26][27][28][29][30], ecological and climatic conditions [31,32].…”
mentioning
confidence: 99%